2023
DOI: 10.1021/acs.jpcb.2c06410
|View full text |Cite
|
Sign up to set email alerts
|

Switching of the Polarity-Sensitive Aggregation Pattern of a Thiosemicarbazone-Based Anticancer Luminophore and Its Involvement in Cellular Apoptosis of the Human Lung Cancer Cell Line

Abstract: Elucidation of the photophysical and biochemical properties of small molecules can facilitate their applications as prospective therapeutic imaging (theragnostic) agents. Herein, we demonstrate the luminescence behavior of a strategically designed potential therapeutic thiosemicarbazone derivative, (E)-1-(4-(diethylamino)-2-hydroxybenzylidene)-4,4-dimethylthiosemicarbazide (DAHTS), accompanied by the illustration of its solvation and solvation dynamics using spectroscopic techniques and exploring its promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…According to the research by Ganorkar et al, , they found that DAHTS existed in the dimer conformation in ACN solvent, and the connection mode of the dimer was given by analyzing the crystal structure.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the research by Ganorkar et al, , they found that DAHTS existed in the dimer conformation in ACN solvent, and the connection mode of the dimer was given by analyzing the crystal structure.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Interestingly, in their experiment, Ganorkar et al reported that DAHTS exhibited a novel and interesting phenomenon of triple fluorescence emission in nonpolar (CYH) and aprotic polar [acetonitrile (ACN)] solvents. 43 It was speculated that the proton-transfer behavior led to this special phenomenon of fluorescence in the experiment. The internal reason for this fluorescence phenomenon and the proton-transfer mechanism in DAHTS still remain not explicit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Lung carcinoma is still a challenging problem. [13][14][15][16][17][18][19][20][21][22][23] It is expected that the development of fluorescent probes can serve the clinical work well, so the clinical application strategy of fluorescence-guided surgery (FGS) can be realized. During the surgical procedure, the fluorescent probes are used for the specific visual imaging of the lesion site to detect and discriminate malignant and normal tissues, which can reduce the surgical trauma and improve the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%